3°. Знайти значення виразу: 3/(√(7+√24) -1)-3/(√(7+√24) +1).

As337 As337    2   02.04.2021 15:16    0

Ответы
artem0941 artem0941  02.05.2021 15:21

3-√6

Пошаговое объяснение:

3/(√(7+√24) -1) -3/(√(7+√24) +1)=3/(√(7+2√6) -1) -3/(√(7+2√6) +1)=3/(√(6+2√6 +1) -1) -3/(√(6+2√6 +1) +1)=3/(√(√6 +1)² -1) -3/(√(√6 +1)² +1)=3/√6 -3/(√6 +2)=(3√6)/(√6)² -(3(√6 -2))/((√6 +2)(√6 -2))=(3√6)/6 -(3(√6 -2))/(6-4)=(√6)/2 -(3(√6 -2))/2=(√6 -3√6 +6)/2=(6-2√6)/2=(2(3-√6)/2=3-√6

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика